Anestesia total intravenosa com propofol associado ao fentanil, lidocaína, cetamina ou fentanil-lidocaína-cetamina em cadelas submetidas à ovariossapingohisterectomia eletiva - Monzem, Samuel (2016)
The aim of this study was to evaluate and to compare the influence of the bolus and of the continuous infusion of fentanyl, lidocaine, ketamine or association of these under the induction and maintenance of total intravenous anesthesia with propofol, cardiorespiratory parameters, the intraoperative and residual analgesia, anesthetic recovery and the incidence of adverse effects in bitches submitted to the elective ovariohysterectomy. 32 bitches were used, premedicated intramuscularly with 0,03 mg/kg of acepromazine and after 30 minutes distributed in four groups, with different analgesic treatments administered by the intravenous mode: the group F received bolus of 0.0036 mg/kg of fentanyl, followed by continuous infusion of 0.0036 mg/kg/h; the group L: bolus of 3 mg/kg of lidocaine, followed by 3 mg/kg/h; group K, bolus of 0.6 mg/kg of ketamine, following by 0.6 mg/kg/h and group FLK bolus and continuous infusion of the three drugs in the doses mentioned previously. Was administered as a bolus of analgesic treatment, followed by induction with propofol and started of continuous infusion and analgesic treatment and propofol. After intubation endotracheal was performed, the animal was positioned sternal, connected to 100% oxygen and kept spontaneously breathing. The maintenance dose was adjusted according to the anesthetic plan and cardiovascular parameters. Intraoperative period was monitored heart and respiratory rate, end tidal carbon dioxide, systolic, diastolic and mean blood pressure, body temperature and the propofol infusion rate. The evaluations were performed 5, 15, 20, 30, 40, 50, 60, 70 and 80 minutes after induction. The infusion of drugs was finished concurrent with the end of the surgery. For evaluation of the anesthetic recovery the times of extubation, decubitus sternal and position quadrupedal were considered, that were measured in minutes starting from the end of the infusions. For the residual analgesia, the animals were appraised for two observers, blind to the treatments, through the analogical visual scale, of the modified scale of Glasgow and of degree sedation of Dobbis that were checked one hour before the surgery and hourly after the extubation, up to a maximum of six hours or until the animal reached the punctuation of 3.3 points or more in scale of Glasgow, by one appraiser. After, analgesic rescue was performed with 25 mg/kg dipyrone intravenous, 0.2 mg/kg meloxicam subcutaneous. It was also observed adverse effects present in the recovery period. All groups produced cardiovascular stability, adequate analgesia and anesthesia recovery to ovariohysterectomy procedure. Respiratory depression was observed in all groups, being most pronounced in the groups containing ketamine. There was no statistical difference being the groups in anesthetic recovery. During the evaluation 50% of the animals of the group L and 25% of the group K presented vomit; 37.5% of the group F and 25% of the group L and K had excessive salivation; 12.5% of the group F and L and 37.5% of the group FLK presented muscular tremors. The fentanyl-lidocaineketamine produced greater analgesia intraoperative and residual for six hours. As a result of respiratory depression is recommended to artificial ventilation